Why start a business in a declining rural area with an ageing society? A UK - NL case study - Heike Delfmann (European Regional Science Association (ERSA), 2014)
People have various motivations for becoming an entrepreneur. A common assumption is that entrepreneurs in deprived or remote regions are more likely to be motivated by necessity, as employment opportunities are limited and people have little to lose in starting their own business. However, demographic changes can also lead to restructuring or motivate people to start a social enterprise. A key step in gaining further insights into entrepreneurship in these areas is developing a better understanding of entrepreneurial motivations. Location decisions taken by firms would rationally include an assessment of regional conditions and developments, which raises the question: what motivates people to start a business in a rural, ageing region? And how do their motivations fit in the opportunity and necessity dimension? Rural Northumberland (UK) and rural Drenthe (NL) are both facing a declining workforce and are strongly ageing. By means of semi structured, face-to-face interviews with entrepreneurs in the two case study regions, the aim is to determine the impact of the regional context on start-up behaviour. In the Netherlands, all rural regions are relatively close to an urban centre in geographical terms and peripheral regions are well connected through infrastructure, providing them a fairly easy link to the urban centres. In England, we find more ?traditional' rural regions, more isolated with weaker links to urbanised areas. By comparing the two regions, which are quite similar on paper but very different on the urban ? rural relation, we assess to what extent the type of rurality affects the decision making process and start-up motivation.
Keywords: M13; O18; R11; 330; ageing; rural; entrepreneurship; in-depth interviews; motivation